2003
DOI: 10.1186/1472-6807-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of HIV-1 protease-inhibitor binding energies by molecular dynamics simulations

Abstract: BackgroundThe accurate prediction of enzyme-substrate interaction energies is one of the major challenges in computational biology. This study describes the improvement of protein-ligand binding energy prediction by incorporating protein flexibility through the use of molecular dynamics (MD) simulations.ResultsDocking experiments were undertaken using the program AutoDock for twenty-five HIV-1 protease-inhibitor complexes determined by x-ray crystallography. Protein-rigid docking without any dynamics produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…10 predicted to have the highest affinity using the molecular dynamics simulation and docking techniques. 6 The AG7088 inhibitor only partially fits into the binding pocket that the substrate would occupy, whereas the inhibitor with the highest binding affinity, L-700,417, mimics the substrate binding mode very well. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…10 predicted to have the highest affinity using the molecular dynamics simulation and docking techniques. 6 The AG7088 inhibitor only partially fits into the binding pocket that the substrate would occupy, whereas the inhibitor with the highest binding affinity, L-700,417, mimics the substrate binding mode very well. …”
mentioning
confidence: 99%
“…6 The affinities have then been used to predict resistance/susceptibility for 1800 HIV-1 protease mutants/inhibitor combinations with greater than 90% accuracy. In a similar fashion, we have calculated the binding affinities of a variety of known HIV-1 protease inhibitors to the TGEV main proteinase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jenwitheesuk et al [20] reported that mutations in HR2 improve structural stability of the HR1/HR2 hairpin complex and may lead to enhancement of ENF resistance when present with resistant HR1 mutations.…”
Section: Emergence Of Enf-resistant Hiv-1 Mutantsmentioning
confidence: 98%
“…The authors reported that Asp f1 and its deletion mutant Asp f1 D (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have been produced as recombinant proteins, and that the deleted aa sequence corresponds to an exposed NH 2 -terminal b-hairpin in Asp f1 protein. The NH 2 -terminal b-hairpin is highly flexible and has an exposed region, folded independently from the protein core.…”
Section: Ribotoxin Toxicity To Cells Ribonuclease Activity and Allermentioning
confidence: 99%